Red‐emissive Dual‐state Fluorogenic Probe for Wash‐free Imaging of Lipid Droplets in Living Cells and Fatty Liver Tissues. Issue 7 (27th February 2023) - Wang, Hui; Zhang, Cuifeng; Hu, Lei; Tang, Fang; Wang, Yaxuan; Ding, Feiyang; Lu, Jingwen; Ding, Aixiang
Abstract: Lipid droplet (LD) dysfunction can result in various diseases, such as nonalcoholic fatty liver disease. Imaging agents built on dual‐state emission (DSE) molecules that fluoresce in both dilute solutions and the aggregated state are receiving attention as this type of probe could provide bright fluorescence signals at variable concentrations, avoiding false signal readout caused by the concentration fluctuation in living systems. Herein, we identified a red emissive molecule featuring DSE, from three newly synthesized molecules, for specific detection of LDs in live cells. The bioimaging abilities have been well confirmed by optical spectroscopies, theoretical calculations, cell experiments, as well as animal studies. The DSE probe is effective for LD detection at concentrations ranging from 1 μM to 100 μM while retaining high brightness and signal fidelity. This study provides a knowledge base for the future design of DSE‐active fluorescent probes for understanding LD‐related diseases. Abstract : L1 is a dual‐state emissive (DSE) molecule showing strong fluorescence in both dilute solutions and the aggregated state. L1 as a DSE probe can specifically image liquid droplets (LDs) in cells and tissues with high brightness at a wide range of concentrations, demonstrating its high applicability in dynamic, complex living systems.